Uncovering Gunung Berkembang Tourism and Samiler Crackers as Sustainable Microenterprises for Kedungudi Empowerment: Ungkap Wisata Gunung Berkembang dan Kerupuk Samiler sebagai Usaha Mikro Berkelanjutan Pemberdayaan Kedungudi - Amin, M. Irwani; Ariani , Suci; Fauziyah, Luluk Putri; Kusumaningrum, Tri Agustin; Firdausi , Rajendra Rafi (Proceedings of The ICECRS, 2023)
The aim of carrying out this service is specifically in the mountain tourism industry and the manufacture of Samiler crackers in Kedungudi, micro businesses are enhanced by empowerment. The service method used is to increase added value, product and process development to encourage innovation in the process of making Samiler crackers. identify and create attractive and sustainable mountain tourism packages. This dedication produces micro-entrepreneurs who have greater capacity and better skills in management, production and marketing. And the resulting essence in the form of environmental destruction prioritizes sustainable product practices in production and mountain tourism, maintaining the balance of the local ecosystem. disturb the environment maintain the balance of the local ecosystem by using sustainable products when creating and developing mountain tourism. Highlights: Enhancing micro-businesses in Kedungudi through value addition and product development for Samiler crackers. Empowering micro-entrepreneurs with improved management, production, and marketing skills in the mountain tourism industry. Prioritizing sustainable practices to prevent environmental degradation and maintain the local ecosystem's balance in both product manufacturing and mountain tourism development. Keywords: Mountain Tourism, Samiler, Micro Business